(untitled) (Journal of the College of Basic Education, 2022)
Human rights have received forms of attention and care in the light of ancient civilizations such as the Greek and Roman civilizations, and the great contributions their thinkers made in the field of human rights considering man as one of the greatest miracles in the world. The nature of the social and political composition of society. As for the ancient Egyptian civilization, its contribution to the field of human rights was clearly manifested in a way that differed from what was the case in the Greek and Roman civilizations, which were characterized by class division and inequality.. The goal of the law applied by the sun god, ruler of Egypt at the time, was to achieve justice. And the realization of truth and honesty on the basis that it is a law housed from heaven.